Model Pemberdayaan Konsumen terhadap Ancaman Bahaya Produk Pangan Tercemar Bahan Berbahaya Beracun di Provinsi Lampung - Ahmad Zazili; Hartono Hartono (Jurnal Hukum IUS QUIA IUSTUM, 2016)
One of the consumer rights is the right for food security. In fact there are still many food products distributed for people not fulfilling the health standard. This research is to study the issues of first: what are the measures taken by government in controlling the food products contaminated by the chemical substances? Second, how is the model of consumer empowerment from the threat of food products contaminated by the chemical additives?  The research method used is the empirical-normative law research. Through the library research and elucidation, the result of the research showed first; the controlling measures of government were by prohibiting the use of Formalin, Borax, Rhodamine B, Methyl Yellow as the food additives, and by controlling the distribution of food products. Second, the model of consumer empowerment that can be done is the education for the consumers by spreading the information and elucidation.